DINAMIKA POPULASI MONYET EKOR PANJANG (MACACA FASCICULARIS) DI HUTAN WISATA ALAS KEDATON TABANAN - Soma, I Gede; Wandia, I Nengah; Suatha, I Ketut; Widyastuti, Sri Karyati; Rompis, Aida LT; Arjentinia, Gede Yudhi (Buletin Veteriner Udayana; Vol. 1 No. 2 Agustus 2009, 2012)
Overall population dynamic were observed in identified individuals between August andOctober 2008, in large group of long failed macaques in the AlasKedaton, Bali. Totalpopulation was 364 monkeys consisted of 54 (14,8%) adult males, 104 (28,6%) adultfemales, 164 (45,1%) juvenile and 42 (11,5%) infant. They were divided into 4 differentsmall social groups i.e., Parking area group, North area group, Centre area group and Southarea group. Ratio of adult male and adult female was 1: 2.Population densitiesof Macaca fascicularisin Alas Kedaton were 30 monkeys / Ha andpopulation natalities were 11, 5%.
Keywords: Macaca fascicularis; juvenile; population dynamic; population density; male-female adult ratio; population natality